2012
DOI: 10.1097/mcg.0b013e3182274375
|View full text |Cite
|
Sign up to set email alerts
|

Can Percutaneous Cholecystostomy be a Definitive Management for Acute Acalculous Cholecystitis?

Abstract: Percutaneous cholecystostomy is an effective procedure and a good alternative for patients unfit to undergo immediate surgery because of severe sepsis or an underlying comorbidity. After patients with AAC have recovered from percutaneous cholecystostomy, further treatment such as cholecystectomy might not be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 13 publications
5
42
0
1
Order By: Relevance
“…Excluding patients with limited life expectancy caused by advanced malignancy or in rare circumstances when PC is contraindicated, PC is considered the treatment of choice for patients who are not candidates for cholecystectomy [2,5,6]. PC has been shown to be lifesaving in high-risk patients [7] and should be considered a reasonable option in the therapeutic spectrum for patients with both acalculous and calculous AC as a temporizing measure while awaiting resolution of sepsis and optimization of comorbidities before performing the elective surgery or also as a definite treatment, especially in acalculous forms [7][8][9]. PC seems especially useful for certain categories of patients such as patients in intensive care (where the prevalence of acalculous cholecystitis can be as high as 10 %) and in pregnant women where medical treatment alone for cholecystitis is often not successful [2].…”
Section: Percutaneous Cholecystostomy and Its Role In Management Acutmentioning
confidence: 99%
“…Excluding patients with limited life expectancy caused by advanced malignancy or in rare circumstances when PC is contraindicated, PC is considered the treatment of choice for patients who are not candidates for cholecystectomy [2,5,6]. PC has been shown to be lifesaving in high-risk patients [7] and should be considered a reasonable option in the therapeutic spectrum for patients with both acalculous and calculous AC as a temporizing measure while awaiting resolution of sepsis and optimization of comorbidities before performing the elective surgery or also as a definite treatment, especially in acalculous forms [7][8][9]. PC seems especially useful for certain categories of patients such as patients in intensive care (where the prevalence of acalculous cholecystitis can be as high as 10 %) and in pregnant women where medical treatment alone for cholecystitis is often not successful [2].…”
Section: Percutaneous Cholecystostomy and Its Role In Management Acutmentioning
confidence: 99%
“…[9] Literatürde bildirilen doğrudan işleme bağlı mortalite oranları %0-3.7 arasında iken, 30 günlük mortalite oranları %36'ya varmaktadır. [3,8,21,22] Bunun nedeninin, PK için seçi-len olguların genellikle cerrahi riski yüksek ve genel durumu kötü olan ağır hastalar olması ve çoğunlukla eşlik eden diğer hastalıkları nedeniyle kaybedilmesi olduğu düşünülmektedir. Bizim olgularımızda işle-me bağlı ya da 30 günlük mortalite (%0) görülmedi.…”
Section: Discussionunclassified
“…13 Our data showed that in such high-risk cases that even when a PC drain was deployed during the first admission, that the need for elective surgery can be selective 31 and that PC drainage can act as definitive management. 32,33 Although the treatment options are competitive, these patient groups are not, however, strictly comparable. As in our study those undergoing an interval cholecystectomy had a lower death rate than those definitively managed with PC drainage, reflecting the inherent physiological differences between these two groups along with commoner deaths from non-biliary causes in PC-treated cases.…”
Section: Discussionmentioning
confidence: 99%